Coping Strategy for Female Workers with Maternal Status: A Study of Lecturer at Sangga Buana University - Pratama, Yudhistira Anugerah; Isnajati, Louisiani Mansoni; Rusmiyandani, Rofi Nuraziz; Philips, Grace Angela (Gaster, 2025)
Background: A coping strategy is an individual's effort to reduce demands or stress. Lecturers at Sangga Buana University utilize various coping strategies. This study aims to measure and describe coping strategies based on two dimensions and eight types outlined by Lazarus & Folkman, namely problem-focused strategies and emotion-focused strategies.  Methods: This study employs a mixed-method approach with a concurrent nested design and identical sampling. The qualitative approach explores in depth the coping strategy selection process among two female lecturers with maternal status, based on statistical measurements using Lazarus & Folkman’s (1984) instrument from the quantitative phase. Qualitative data analysis includes transcription, classification, and drawing conclusions.  Results:The findings present quantitative data in tabular form and describe the coping strategies used by the research subjects. Both subjects applied strategies from both coping dimensions but in different forms. These coping strategies could either facilitate or hinder each other in the coping process.  Conclusion: The study reveals that lecturers who are also mothers at Sangga Buana University employ both problem-focused and emotion-focused coping strategies to manage stress. These strategies influence their social functioning and role performance. The subjects adaptively utilize all coping dimensions, adjusting to environmental demands and available resources, with the aim of restoring balance and mitigating psychological and environmental stressors.